Cycle-to-Cycle Switching Endurance Variability in Vertically Aligned Nanocrystalline Molybdenum Disulfide: Computational Insights - Turfanda, Aykut; Ünlü, Hilmi (IOP, 2024)
We propose a model to depict abrupt transient changes in the endurance test results of a resistive switching device comprising vertically oriented layers of nanocrystalline transition metal dichalcogenide layers with respect to the substrate. We aim to relate and understand the so-called resistance drift occurring in the endurance test results with our model, which is further tested using density functional theory simulations. We conclude that the relationship between resistance drift and skin effect is dominated by alternating electric current resistance and surface resistance. These results are crucial for understanding the resistance drift occurring in several resistive switching devices operating based on defects and ions.
Keywords: Memristor; Endurance; Resistive Switching